Standardisation of Foreign Labour Investigation of Mineral Mining Company - Agus Lanini; Sutarman Yodo; Ikhsan Syafiuddin; Muhammad Ahsan Samad (Sriwijaya Law Review, 2024)
The era of free trade, including trade in labour services, has been confirmed in the General Agreement on Trade in Services, which guarantees everyone the right to work anywhere, including in Indonesia, without discrimination while complying with Indonesian national laws. However, the entry of foreign workers raises several problems in the social and economic fields as well as security and order regarding the placement of these foreign workers. Regulation over the workers is ineffective because only a few authorities are delegated to the local government. This study aims to determine and measure the effectiveness of supervision of foreign workers by the Department of Manpower and Transmigration of the Central Sulawesi Province and to describe the supervision standards of foreign workers that already exist and should be implemented. The empirical legal research is used to examine the provisions of the supervision of foreign workers through observation, in-depth interviews, and focus group discussions. The data that have been collected are processed, classified, qualified, and then analysed qualitatively. The study found that only a few authorities regulated the duties and functions of supervision. The standard of foreign worker supervision has yet to be specifically regulated, so it still faces obstacles regarding coordination between the authorised agencies.